If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 * 8 + -6 = g Multiply 7 * 8 56 + -6 = g Combine like terms: 56 + -6 = 50 50 = g Solving 50 = g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1g' to each side of the equation. 50 + -1g = g + -1g Combine like terms: g + -1g = 0 50 + -1g = 0 Add '-50' to each side of the equation. 50 + -50 + -1g = 0 + -50 Combine like terms: 50 + -50 = 0 0 + -1g = 0 + -50 -1g = 0 + -50 Combine like terms: 0 + -50 = -50 -1g = -50 Divide each side by '-1'. g = 50 Simplifying g = 50
| 9x-3=4x+18 | | 8+2*5=m | | (-7)+(-9)= | | 3y^3+4y^2-6x-8=0 | | 7(x-4)=12 | | f(x)=ln(x^2-5*x+6) | | 4(b-6)=6 | | fx=8cos(-x/4) | | 10+5y=4 | | 7(1/2)*x=7/8 | | 7(1/2)^x=7/8 | | 8x-15=5x-12 | | -x-2=-4x+7 | | q+2=6q | | 6q+0(1-q)= | | 2(3a+6)=4(3-7a)+6a | | f(x)=5e^2x-e | | 3q+2(1-q)= | | 6x+16=10x+44 | | 1.6(x-3)=-80 | | .6*x+4=7 | | 4x-13-6x+4=3-9X-7+3x | | 8x-2=4y | | A=p+petfory | | x+(2x+1)=-2 | | 0.4t-0.3=1.8-0.1(2t+9) | | 4x^3-2x^2+3=0 | | 3(y-3)-2=7 | | 2x+2y=81 | | 2n/4n | | 4(a-3)=6a+11 | | 4a-3=6a+11 |